FOTODEGRADASI METILEN BIRU DENGAN SINAR UV DAN KATALIS Al2O3 - Widihati, Ida Ayu Gede; Diantariani, Ni Putu; Nikmah, Yuliana Farhatun (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 1 Januari 2011)
The research was conducted to observe the photodegradation of methylene blue by UV light and Al2O3 catalyst. The research determinated the optimum Al2O3 catalyst weight, the optimum pH, the optimum radiation duration and the effectivity of photodegradation at optimum conditions. Degradation of methylene blue were analyzed by UV-Vis spectrophotometer. The results showed that the optimum Al2O3 catalyst weight was 40 mg the optimum of pH was 11, and the optimum of radiation duration was 4 hours. The effectivity of photodegradation was (30.22 ± 1.17)%.
Keywords: photodegradation, methylene blue, Al2O3 catalyst